Chemogenetic stimulation of the Gi pathway in astrocytes suppresses neuroinflammation - Jae‐Hong Kim; Md Habibur Rahman; Won Ha Lee; Kyoungho Suk (Wiley, 2021)
Abstract Engineered G protein‐coupled receptors (GPCRs) are commonly used in chemogenetics as designer receptors exclusively activated by designer drugs (DREADDs). Although several GPCRs have been studied in astrocytes using a chemogenetic approach, the functional role of the astrocytic Gi pathway is not clear, as the literature is conflicting depending on the brain regions or behaviors investigated. In this study, we evaluated the role of the astrocytic Gi pathway in neuroinflammation using a Gi‐coupled DREADD (hM4Di). Gi‐DREADD was expressed in hippocampal astrocytes of a lipopolysaccharide (LPS)‐induced neuroinflammation mouse model using adeno‐associated viruses. We found that astrocyte Gi‐DREADD stimulation using clozapine N‐oxide (CNO) inhibits neuroinflammation, as characterized by decreased levels of proinflammatory cytokines, glial activation, and cognitive impairment in mice. Subsequent experiments using primary astrocyte cultures revealed that Gi‐DREADD stimulation significantly downregulated LPS‐induced expression of Nos2 mRNA and nitric oxide production. Similarly, in vitro calcium imaging showed that activation of the astrocytic Gi pathway attenuated intracellular calcium transients triggered by LPS treatment, suggesting a positive correlation between enhanced calcium transients and the inflammatory phenotype of astrocytes observed in the inflamed brain. Taken together, our results indicate that the astrocytic Gi pathway plays an inhibitory role in neuroinflammation, providing an opportunity to identify potential cellular and molecular targets to control neuroinflammation.